Democracy in England - Spearman, Diana (London, 1957)
EVERYONE in England now agrees that democracy is not merely the best but the only possible form of government for any civilized state. The right of the majority to choose the Government is now so completely accepted that a permanent commission has been set up to keep constituencies arithmetically equal, and the idea that every citizen shall count as one, and none as more than one, has been carried to the extent of abolishing the representation of the Universities in the House of Commons and depriving business men of the right to vote in the constituencies in which they have business premises as well as in those in which they live. The Crown no longer has power, only influence, and the veto of the House of Lords has been reduced to delaying for twelve months any Bill that has passed the House of Commons. The spirit of politics corresponds to the forms; the local influence of great landowners and large employers of labour, which existed up to the 1914 war, has in political matters, vanished. It is difficult if not impossible for a peer to be Prime Minister or Foreign Secretary or indeed to hold any major Cabinet office, except that of Lord President of the Council, an office whose importance is unperceived by the general public. It is one of the chief preoccupations of the constituency associations, particularly in the Conservative party, to make the form and spirit of the associations as democratic as possible. The word 'democratic' in popular But what has become a synonym for admirable or desirable.
Keywords: Democracy